On the Domain of the Triangle on the Spaces of Null, Convergent, and Bounded Sequences - Naim L. Braha; Feyzi Başar (Abstract and Applied Analysis)
We introduce the spaces of -null, -convergent, and -bounded sequences. We examine some topological properties of the spaces and give some inclusion relations concerning these sequence spaces. Furthermore, we compute -, -, and -duals of these spaces. Finally, we characterize some classes of matrix transformations from the spaces of -bounded and -convergent sequences to the spaces of bounded, almost convergent, almost null, and convergent sequences and present a Steinhaus type theorem.